2020
DOI: 10.1590/1413-812320202511.00222019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Chronic Obstructive Pulmonary Disease in Brazil: a systematic review and meta-analysis

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is among the leading causes of morbidity and mortality in developing countries; however, few systematic reviews are available in the literature. This review examines the prevalence of COPD in the Brazilian population. For this purpose, a systematic review and meta-analysis was conducted of epidemiological observational studies indexed in the databases PubMed, Cochrane, Ovid, Scopus, ScienceDirect, SciELO, Lilacs, and Google Scholar published up to May 2018. The prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
5
0
8
Order By: Relevance
“…Alterações da mecânica pulmonar resultam nas principais manifestações clínicas de dispneia, tosse e expectoração crônica. (2,3) A DPOC aumenta a suscetibilidade a distúrbios do sono. A predisposição ao sono de má qualidade em pacientes com DPOC possivelmente ocorre em virtude de anormalidades das vias aéreas superiores e inferiores.…”
Section: Introductionunclassified
“…Alterações da mecânica pulmonar resultam nas principais manifestações clínicas de dispneia, tosse e expectoração crônica. (2,3) A DPOC aumenta a suscetibilidade a distúrbios do sono. A predisposição ao sono de má qualidade em pacientes com DPOC possivelmente ocorre em virtude de anormalidades das vias aéreas superiores e inferiores.…”
Section: Introductionunclassified
“…In this study, individuals who reported having COPD, aged between 40 and 59 years, were signi cantly more likely to use rehabilitation therapies when compared to the other reference categories. COPD is among the leading causes of morbidity and mortality in developing countries 29 . In Brazil, COPD is among the ten leading causes of death 29 .…”
Section: Discussionmentioning
confidence: 99%
“…COPD is among the leading causes of morbidity and mortality in developing countries 29 . In Brazil, COPD is among the ten leading causes of death 29 . The specialized literature indicates that pulmonary rehabilitation improves exercise capacity, reduces dyspnea, and improves the overall quality of life, and its bene ts surpass any other therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma and COPD have multifactorial causes and are associated with exposure factors related to the occupational or home environment (tobacco and wood smoke), unfavorable socioeconomic status, and genetic factors [7][8][9][10] . According to the literature, air polluting agents are related to lung diseases and respiratory symptoms 11 .…”
Section: Introductionmentioning
confidence: 99%